REMOTE SENSING DATA ANALYSIS WITH VALIDATION BY NUMERICAL MODEL FOR DETECTING SUSPENDED PARTICULATE MATTER CONCENTRATION IN COASTAL WATERS OF THE RED RIVER DELTA, VIETNAM - Thao, Nguyen Van; Vinh, Vu Duy; Huong, Do Thi Thu; Gouramanis, Chris (Vietnam Journal of Marine Science and Technology, 2018)
In this study, a set of optical and Suspended Particulate Matter data measured in the coastal waters of the Red river delta is examined to develop empirical and semi-analyzed algorithms to process satellite remote sensing data. A scene of high resolution satellite images of Landsat-8 OLI is used to test the algorithm for determining the distribution of Suspended Particulate Matter concentration in marine waters. A numerical model is also developed to calculate Suspended Particulate Matter transportation in the study area and calibrate statistics measured at certain monitoring stations of water flow and Suspended Particulate Matter from river discharged into the sea. The results on Suspended Particulate Matter concentrations in the coastal waters of the Red river delta determined from the satellite image algorithms and those of the numerical model are compared and evaluated.